Science and society in the face of the new security threats - Sharpe, Mary; Agboluaje, Abimbola (NATO security through science series. Human and societal dynamics, 2006)
Contains papers that explore the challenges faced by the science establishments in the new security environment across a range of NATO countries. This work examines possible solutions by looking in closer detail at some national case studies. It sets out the importance of the NATO Security Through Science programme in the new security environment.